DEV-07. THE LATIN-AMERICAN BRAIN TUMOR BOARD (LATB) TELECONFERENCE: RESULTS OF A WEB-BASED SURVEY TO EVALUATE PARTICIPANT EXPERIENCE AND THE PROGRAM. Issue 2 (22nd June 2018) - Abu Arja, Mohammad H; Coven, Scott; Stanek, Joseph R; Morales La Madrid, Andrés E; Lassaletta, Alvaro; Bartels, Ute; Qaddoumi, Ibrahim; Finlay, Jonathan L; Osorio, Diana S
Abstract: PURPOSE: The LATB is a weekly teleconference operating over 3.5 years connecting pediatric neuro-oncologists from high-income countries with pediatric subspecialists from 20 Latin-American countries. This survey explored the participants' experience utilizing this resource. METHODS: A web-based questionnaire was distributed to 159 participants through email and www.Cure4Kids.org . RESULTS: Ninety-five respondents (60%) from all the 20 participating countries completed the survey. Sixty-one reported frequent-attendance (≥ 1 per month), 23 reported infrequent-attendance (< 1 per month), and 11 never participated. The main barriers to attendance were the subspecialist's respective workload (64%), the timing of the teleconference (38%), and internet connectivity problems (29%). Subspecialist's workload amount was more commonly reported as a barrier compared with other barriers, in both the frequent and infrequent-attendance groups (p<0.05), with the exception of the timing of the meeting in the infrequent-attendance group. More than 80% found the frequency and duration of the teleconference were sufficient. Utilizing Spanish as the primary language was reported to enhance the teleconference recommendations by 93% of the respondents. The recommendations were reported to always or almost always fit the local circumstances by 84%, moreover; 99% of attending respondents found the teleconference provides a continuing medical education opportunity. Finally, 83% agreed to the need to include more subspecialties into LATB especially: neuroradiology, neuropathology, neurosurgery, and radiation-oncology. CONCLUSION: Participants found that weekly, one-hour sessions were sufficient to review the requested cases. Utilizing the participants' first language makes the recommendations clearer and easier to follow. Physician workload is the main barrier to participate in the teleconference.